(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the issue of developing intercultural communication competence of future English teachers based on an axiological approach. The study reveals the inextricable link between intercultural communication competence and values ​​and justifies didactic strategies that can be used in the process of training English teachers. The results of the study show that the axiological approach serves to increase the professional competence of future teachers by forming tolerance, cultural empathy, and respect for values ​​in the educational process. The results of the article are of practical importance in improving the methodology of teaching foreign languages ​​in higher education institutions.